MENINGKATKAN KETERAMPILAN BERBAHASA PERANCIS BAGI PEMANDU WISATA PEMULA - Endang Ikhtiarti; Diana Rosita; Indah Nevira Trisna; Setia Rini (Education Language and Arts (ELA), 2022)
The aim that want to be raiche in this activity is to give knowledge and conception to the students of SMK N 3 Bandarlampung about how to be professional and good guide touristique in French. The method use in this training is lecture method, question answer method and practice. The participants of training hear the explanation that given from the resource person accurately and enthusiasly, helping by power point media, reflected by LCD. Then the participants of training are given the time to practice to be a guide, play role, such as guide in their group. After that they are given the time to ask to resource person about the subject not enough clearly. And then the resource person respond all of that questions. In this activity is given Pre-Test and Post–Test to know how the knowledge of participant before and after training. The objectif of this public service is the students grade x of SMKN 3 Bandarlampung that studying French language in vocational program on SMK Curriculum, they are 32 persons. The place of public service is realized in SMK N 3 Bandarlamung on jl. Cut Mutia, Gulak Galik, kecamatan Teluk Betung Utara 35212 Bandarlampung. The public service is realized during 3 days 15 until 17 june 2022. The result of the Pre-Test and Post-Test describe there is a progress. The average of Pre- Test 2,5 and Post- Test 61,9375. That case indicate the there is a raise of note 4,4375 point. While hoping for this activity is the student SMKN 3 BDL can understand and know how to be a good and professional guide accordance criteria standart that wants to be.